Optimalisasi Literasi Sastra dan Karakter Ekologis Melalui Outdoor Learning di Madrasah Ibtidaiyah Nahdlatul Ulama 01 Sigedong, Kabupaten Tegal - Syamsul Falah; Moh. Wifaqul Idaini (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2025)
This qualitative study aims to describe the application of outdoor learning methods in improving the poetry writing skills and environmental awareness of fourth-grade students at Madrasah Ibtidaiyah Nahdlatul Ulama 01 Sigedong, Tegal Regency. Data were collected through observation, semi-structured interviews, and documentation, with analysis using reduction, data presentation, verification. The results showed a significant increase in poetry writing skills, with observation scores increasing from 56% (poor) in the first meeting, 82% (good) in the second meeting, to 92% (very good) in the third meeting. The implementation of outdoor learning motivates students through direct observation of the environment, resulting in poetry that is rich in meaning and imagination. In addition, the integration of environmental awareness through activities such as “Healthy and Clean Friday” and daily pickets can shape ecological conservation awareness. This study contributes to the importance of implementing outdoor learning as an innovative and effective method in Indonesian language learning and strengthening environmental awareness.